2012
DOI: 10.1002/lary.23369
|View full text |Cite
|
Sign up to set email alerts
|

Objective assessment in residency‐based training for transoral robotic surgery

Abstract: Objective To develop a robotic surgery training regimen integrating objective skill assessment for otolaryngology and head and neck surgery trainees consisting of training modules of increasing complexity and leading up to procedure specific training. In particular, we investigate applications of such a training approach for surgical extirpation of oropharyngeal tumors via a transoral approach using the da Vinci Robotic system. Study Design Prospective blinded data collection and objective evaluation (OSATS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 39 publications
0
53
0
Order By: Relevance
“…The training program we introduced includes the common elements of didactics, skills training, and operative experience, which we found described in structured training curricula for other specialties. While we found two other descriptions of structured modules for training residents in the field of head and neck surgery, notably these modules focused solely on training exercises in an inanimate robotics laboratory setting [11,12]. The structured curriculum described in this report differs by additionally focusing on training in didactics and operative modules.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The training program we introduced includes the common elements of didactics, skills training, and operative experience, which we found described in structured training curricula for other specialties. While we found two other descriptions of structured modules for training residents in the field of head and neck surgery, notably these modules focused solely on training exercises in an inanimate robotics laboratory setting [11,12]. The structured curriculum described in this report differs by additionally focusing on training in didactics and operative modules.…”
Section: Discussionmentioning
confidence: 93%
“…While no two curricula were exactly the same, common elements across the many programs could be identified. In otorhinolaryngology, there were two prior descriptions of structured modules, based solely in a robotic skills training laboratory [11,12]. However, in the other curricula, important structured elements include didactics teaching, skills practice in laboratory settings, and progressive surgical skills development in the operating room.…”
Section: Resultsmentioning
confidence: 99%
“…24 We used a cutoff of 28 on the OSATS scale to group surgeons, because this represents 80% of the maximal OSATS score, and previous studies in other specialties have shown that trained staff surgeons generally scored at least 80% on global rating scales. 25,26 Furthermore, this cutoff has previously been used as a competency benchmark in laparoscopic hysterectomies. 27 In addition to analyzing the entire procedures, we also analyzed operative substeps to assess whether GERT analysis allows the detection of procedure steps that are more prone to technical errors.…”
Section: Discussionmentioning
confidence: 99%
“…A future study will include Otolaryngology-Head and Neck residents training in TORS to determine the effectiveness of the system for non-expert / novice surgeons. Currently, methods of training residents on the daVinci for TORS [16] typically involve resection of an embedded sphere from tongues of porcine animal phantoms, and results are evaluated by measuring margins surrounding the target from the resected sample. Overlay of the tumor in addition to subsurface information would assist in achieving adequate negative margins, crucial to prevent recurrence of disease in clinical practice.…”
Section: Discussionmentioning
confidence: 99%